ELEMENTARY AND GRAMMAR EDUCATION IN LATE MEDIEVAL FRANCE - Lynch, Sarah B. Link ([S.l.])
1 online resource
Keywords: The fourteenth and fifteenth centuries saw a marked increase in the availability of elementary and grammar education in Europe. In France, that rise took the form of a unique blend of trends also seen elsewhere in Europe, ranging from Church-dominated schools to independent schools and communal groups of teachers. Lyon, long a crossroad of ideas from north and south, was home to a particularly interesting blend of approaches, and in this book Sarah Lynch offers a close analysis of the educational landscape of the city, showing how schools and teachers were organised and how they interacted with each other and with ecclesiastical and municipal authorities.